Natural plant products: an alternative to oral dog care? (Research, Society and Development, 2020)
Periodontal disease is one of the most common and prevalent oral diseases in dogs. With the increasing closeness between man and the animals of company, the care with the health and well-being of those animals also increase. Being the bacterial plaque the main cause of periodontal disease, oral care performed by dog owners are essential for the prevention and control of this disease. There are a lot of alternatives, developed exclusively for animal use, which assist in oral hygiene. There are data on the use of active natural products in the prevention of halitosis, dental plaque and calculus, in the form of antiseptic substances, but the volume of information is still scarce. Natural substances, used since immemorial times for treatment of diseases, have the potential to integrate oral care products, such as main or adjuvant active agent in the formulation of the most varied compounds. This is the result of desirable actions in oral and dental therapies, as anti-inflammatory, healing and antimicrobial. This article reviews the information available on the subject and seeks to indicate what is possible to do overcome the gap between research and application of these products on a day-to-day basis.